Computer-aided control design systems : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Industrial Management and Engineering at Massey University - Nguyen, Thi Minh Phuong (Massey University, 1976)
This thesis is concerned with the application of computer-aided design to classical control theory. In classical control theory, much of the effort of control system design is concerned with the generation of charts for such aspects as time response, root locus and frequency response characteristics. These charts are time consuming to prepare by hand, even though short cut techniques are often available to obtain sketches which closely approximate the actual characteristics. A digital computer is able to assist in these conventional design procedures by generating the appropriate charts for inspection by the designer, thereby taking much of the manual effort out of the design processes. This thesis describes the development of an interactive design package. Software for computer-aided control system design has been programmed to operate, via a visual display terminal, in an online interactive mode. The control designer, using the terminal console, is able to specify certain designs and evaluate their effectiveness in terms of the various graphical analyses produced by the computer and displayed on the screen of the terminal.
Keywords: Computer-aided design